If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7m + -3) = -34 Reorder the terms: 2(-3 + 7m) = -34 (-3 * 2 + 7m * 2) = -34 (-6 + 14m) = -34 Solving -6 + 14m = -34 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 14m = -34 + 6 Combine like terms: -6 + 6 = 0 0 + 14m = -34 + 6 14m = -34 + 6 Combine like terms: -34 + 6 = -28 14m = -28 Divide each side by '14'. m = -2 Simplifying m = -2
| t=128.91+.32m | | 11x-10=360 | | 49-3m=4m+14m | | 109=n^2-2n-11 | | 5(2y+3)=-5 | | X=-9(-1/2)-1 | | 4x+3y+2x+5y= | | 2.3=6.3-0.8x | | 1.5x+5=6x+4 | | y/1=9 | | t(t)=125 | | 2(4a-7)=50 | | 6X^2+2X=15 | | 20/2=2 | | (630/90/?=1 | | 38=4x+8 | | 5=w-8aforw | | 20-4/10x=0 | | 50x+130x=360 | | -5+n=-1.2 | | 25d+4=-6 | | 3n*2=18 | | 4a-3=a+15 | | 5=w-8a | | 2x+8=7x-36 | | 7-(2x+5)=5-3(1-2x) | | 121-(-6)=6 | | (27x+10)=29x | | 3p=1+2p-6 | | 4(2y+2)=-16 | | 132=93+(9x+3) | | Z/5-7=3|1/3 |